Penggunaan Media Google Meet dalam Meningkatkan Motivasi Belajar pada Masa Pandemi Covid-19 - Sri Astutik, Ida (Jurnal Didaktika Pendidikan Dasar, 2021)
The purpose of this study is to describe the empowerment of learning media google meet as one of the remote learning tools that can increase the motivation of students’ learning during the covid-19 pandemic. This research is a descriptive quarative research. Data collection techniques are conducted with observations, interviews, and questionnaires on the use of Google Meet media. This research was conducted in grade V of SDN Minggiran I, Kediri Regency. Data analysis techniques are performed with Milles & Huberman interactive analysis. The results showed that the application of Google Meet media in distance learning activities during the covid-19 pandemic had a positive impact on students’ learning motivation. This shows that Google Meet media provides benefits for teachers and students because of the teaching and learning process that can interact directly so as to make online learning more practical and effective. This direct interaction also increases the involvement and activeness of students during online learning during the Covid-19 pandemic.